INCREASING GROWTH AND PRODUCTION OF PEANUT PLANTS (Arachis hypogaea L.)THROUGH PROVIDING LIQUID ORGANIC FERTILIZER (POC) FROM CATFISH FARMING WASTEWATER AND VERMICOMPOST FERTILIZER - Syahriandi Akbari; Fuad Balatif; Nurhayati; Darius El Pebrian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aimed to evaluate the effect of liquid organic fertilizer (POC) from catfish farming wastewater and vermicompost on the growth and production of peanut (Arachis hypogaea L.) plants. The study was conducted in the experimental field of the Faculty of Agriculture, Al Washliyah University using a factorial Randomized Block Design (RBD) with two factors, namely the dose of POC (0, 150, 300, and 450 ml/plot) and the dose of vermicompost (0, 1, 2, and 3 kg/plot). The parameters observed included plant height, number of productive branches, and pod weight per plot. The results showed that the application of POC, vermicompost, or a combination of both did not have a significant effect on all observed parameters. Although the highest treatment showed an increasing trend in the average observed value, the results were not statistically significantly different from the control. This is thought to be caused by the relatively low nutrient content of organic fertilizers and their volatile nature and not being able to optimally meet plant nutritional needs.